Nasal airflow system - Chiang, Yok Peng (Penerbit UTM, 2008)
Voice is a very important element throughout our life. Everyday we communicate with other people by talking, express our feelings by singing, laughing and shouting. However, with an inaccurate speech production, miscommunications or even misunderstanding can happened. Speech production requires a complex coordination of the articulators, which included the larynx, pharynx, velum, lips, teeth and hard palate, and also the tongue. Patients of inaccurate speech production normally were caused by accidents or since born or under other special reasons. It was long ago since the scientists started to show their interest in speech rehabilitation. Researches have been done and finally they came out with the equipment called the nasal airflow system. This nasal airflow system works by comparing the patient's nasal airflow and voice reading with the normal sample provided by a normal speech person and displaying the results in a personal computer. Normally this system is helpful in speech therapy and also in singing teachers' studios. An example of the nasal airflow system that is on the market now is shown in Fig. 9.1. Nasal Airflow System does not stand-alone. Typically, it is combined with Linguagraph (a clinical electropalatography system), Laryngograph (measures function of larynx) and also Videofluoroscopy (detects the movement of the velum and tongue).